2017
DOI: 10.1007/s00405-017-4854-7
|View full text |Cite
|
Sign up to set email alerts
|

Sialendoscopy in treatment of adult chronic recurrent parotitis without sialolithiasis

Abstract: Sialendoscopy appears to reduce the symptoms of chronic recurrent parotitis. While total permanent symptom remission is rare, sialendoscopy can be considered a safe and relatively efficacious treatment method for this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 26 publications
(38 reference statements)
0
6
0
Order By: Relevance
“…Another study showed that retroductal application of corticosteroids was effective in patients with chronic recurrent sialadenitis and Sjögren syndrome. 15 16 17 In contrast, Jokela et al 16 reported that steroid irrigation did not provide additional benefit compared to saline irrigation; however, they conducted single-dose steroid injections, which were not sufficient to determine the efficacy of the drug. 16 Another variable to consider would be the timing of the intervention, since inflammatory gland changes vary widely depending on the duration or severity of disease.…”
Section: Discussionmentioning
confidence: 97%
“…Another study showed that retroductal application of corticosteroids was effective in patients with chronic recurrent sialadenitis and Sjögren syndrome. 15 16 17 In contrast, Jokela et al 16 reported that steroid irrigation did not provide additional benefit compared to saline irrigation; however, they conducted single-dose steroid injections, which were not sufficient to determine the efficacy of the drug. 16 Another variable to consider would be the timing of the intervention, since inflammatory gland changes vary widely depending on the duration or severity of disease.…”
Section: Discussionmentioning
confidence: 97%
“…During sialoendoscopy, saline and anti-inflammatory corticosteroids were used as irrigating solutions. The administration of irrigating solutions, such as corticosteroids, antibiotics, and saline 11 , is intended to remove debris and dilate the duct by hydrostatic pressure to facilitate visualisation 9 , in addition to having therapeutic properties, such as anti-inflammatory and antibiotic actions 9 . Corticosteroids have anti-inflammatory and antiproliferative effects, significantly reducing the formation of primary strictures or their recurrence 1,13 .…”
Section: Discussionmentioning
confidence: 99%
“…This heteroplasia may have a congenital 6,7 or acquired origin, characterised by dilation of the salivary duct, which frequently occurs secondary to obstruction caused mainly by sialolithiasis and strictures of the duct 8 . They can cause an increase in recurrent swelling in the affected duct region 9 , sometimes followed by painful symptoms not associated with eating 6 , making the differential diagnosis with other diseases is essential. 8 Hereditary factors were considered a central element in the development of ectasia 7 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another prospective study by Jokela et al [ 29 ], has shown no significant difference observed in a group of patients receiving 1 mL of hydrocortisone 125 mg/mL and the group receiving 1 mL of isotonic saline solution intraductally, concluding that no additional benefit in symptom relief were found from a single-dose intraductal steroid.…”
Section: Discussionmentioning
confidence: 99%